Pembelajaran Terjemah Bahasa Arab Untuk Santri Boarding School MAN 2 Kota Bima - Muslimin Muslimin; Nurul Zuhriyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Arabic plays an important role in Islamic education as it is the primary language of major religious sources such as the Qur’an, hadith, and classical Islamic literature. Therefore, the ability to translate Arabic texts is an essential competence for students in Islamic boarding schools to understand Islamic knowledge independently. This study aims to analyze the implementation of Arabic translation learning and examine students’ competencies in the Boarding School of MAN 2 Kota Bima. This research employed a descriptive qualitative approach. Data were collected through participant observation, in-depth interviews, and documentation. Data validity was ensured through triangulation techniques, while data analysis followed the model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The results show that Arabic translation learning in the boarding school is implemented through several complementary methods, namely the grammar–translation method, the direct method, the Tamyiz method, and the integration of digital learning media through the Quizizz platform. These approaches help students understand Arabic sentence structures, identify grammatical functions, and produce more accurate and contextual translations. In addition, the learning process contributes to the development of students’ character, learning creativity, and mastery of translation skills. Therefore, the combination of varied learning methods and the use of digital technology can effectively improve students’ Arabic translation competence.